Indigenous Church: A Pauline Response - Baptist, Antony John (Asian Horizons, 2025)
This paper explores the concept of the Indigenous Church through a Pauline lens, examining how the early Christian communities in Paul’s letters exhibit characteristics of indigenous churches. By analysing Paul’s ministry and writings, the study highlights key aspects of Pauline churches, such as the local assembly, the house church model, and the inclusivity of marginalised groups. Additionally, the paper argues that Paul’s theology, particularly his teachings on the passion, death, and resurrection of Jesus, developed in response to the specific social contexts and challenges of early churches. The study concludes that contemporary indigenous churches should adapt their theology to their own cultural and social context, in a manner similar to Paul’s contextual approach to church issues.